A multiscale inflammatory map: linking individual stress to societal dysfunction - Vodovotz, Yoram; Arciero, Julia; Verschure, Paul F. M. J.; Katz, David L. (Frontiers in Science, 2024)
As populations worldwide show heightened stress, understanding emerging links among stress, inflammation, cognition, and behavior is vital to human and planetary health. We hypothesize that inflammation is a multiscale driver connecting stressors that affect individuals to large-scale societal dysfunction and ultimately to planetary-scale environmental impacts. We propose a ‘central inflammation map’ hypothesis to explain how the brain regulates inflammation and how inflammation impairs cognition, emotion, and action. According to our hypothesis, these interdependent inflammatory and neural processes and the inter-individual transmission of environmental, infectious, and behavioral stressors – amplified via high-throughput digital global communications – can culminate in a multiscale, runaway, feed-forward process that could detrimentally affect human decision-making and behavior at scale, ultimately impairing the ability to address these same stressors. This perspective could provide non-intuitive explanations for behaviors and relationships among cells, organisms, and communities of organisms, potentially including population-level responses to stressors as diverse as global climate change, conflicts, and the COVID-19 pandemic. To illustrate our hypothesis and elucidate its mechanistic underpinnings, we present a mathematical model applicable to the individual and societal levels to test the links between stress, inflammation, control and healing, and the implications of transmission, intervention (e.g., via lifestyle modification or medication), and resilience. Future research is needed to validate the model’s assumptions, expand the factors/variables employed, and validate it against empirical benchmarks. Our model illustrates the need for multilayered, multiscale stress mitigation interventions, including lifestyle measures, precision therapeutics, and human ecosystem design. [...]